Attitudes to National Identity Supply and Support Dynamics of Four Malaysian Prime Ministers - Suhaimi Shahnon (PERDANA LEADERSHIP FOUNDATION, 2014)
The central aim of this study is to develop and conduct a systematic research of values, attitudes, attributes and behaviour patterns within Malaysia polities. Academically driven but designed to feed into key Malaysian policy debates, the study aims to explain how people's social values, cultural norms and behaviour patterns are distributed, the way in which they differ within and between regions throughout the country, and the direction at which they are changing.